USING CLASSDOJO AS A TECHNOLOGY-ENABLED FEEDBACK TO PROMOTE STUDENTS’ POSITIVE BEHAVIORS - Diana Luspa (Jurnal Dosen Universitas PGRI Palembang, 2016)
Abstract: Verbal feedback was no longer effectively addressed to ET 11-1 level Term II/2016. It was very difficult to change their habits, using their local language almost most of the time, being not able to stay away from their gadgets, talking about random topics in their group discussions, talking out of turn that made the classroom so noisy, and to make it worse some students liked to say some impolite words. However, they excelled academically. ClassDojo was used to effectively deal with the students behaviors in the classroom. This free mobile application allows teachers to award “positive behaviors” points for individual students’ behaviors - positive feedback and to work more on students’ need work behaviors – need work feedback, Williamson (2016). This 16-meeting study investigated how ClassDojo as a technology-enabled feedback was successfully infused to encourage the development of students’ self awareness to manage their behaviors in the classroom. It was illustrated from the chart that the individual students’ positive behavior gained a gradual increase and the individual students’ need work behavior steadily decreased. Students found it motivating and fun to see the changes on their individual feedback. It was strengthened by the questionnaires distributed to the students. It is hoped that this technique will be tried out by many teachers and found to be beneficial for both teachers and students. Education goes beyond just a test score to developing who the student is as a person. Teachers need to build students’ character, to encourage the students to engage with feedback and formulate actions to improve future learning. Keywords: ClassDojo, Feedback, Behaviors